2022
DOI: 10.1002/rmb2.12445
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic loss of the Y chromosome and men's health

Abstract: Background Although Y chromosomal genes are involved in male sex development, spermatogenesis, and height growth, these genes play no role in the survival or mitosis of somatic cells. Therefore, somatic cells lacking the Y chromosome can stay and proliferate in the body. Methods Several molecular technologies, including next‐generation sequencing and multiplex PCR‐based assays, are used to detect mosaic loss of the Y chromosome (mLOY) in the blood of men. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Mosaic loss of chromosome Y (mLOY), the most common form of aneuploidy relating to genome instability in non-malignant diseases, can occur in all age groups (12) but is most prevalent in older males. Smoking is a potential risk factor for mLOY in blood cells (13).…”
Section: )mentioning
confidence: 99%
“…Mosaic loss of chromosome Y (mLOY), the most common form of aneuploidy relating to genome instability in non-malignant diseases, can occur in all age groups (12) but is most prevalent in older males. Smoking is a potential risk factor for mLOY in blood cells (13).…”
Section: )mentioning
confidence: 99%
“…Loss of Y chromosome (LOY) is one of the most common somatic mutations that can occur at any stage of a healthy male individual's life as a normal aging process, and its frequency increases over time. Gradually expanding studies have revealed that LOY may be associated with a variety of health issues, such as cancer, cardiovascular disease, age-related disorders, and smoking status [14][15][16]. In recent years, methods for the detection and analysis of LOY have been updated and re ned, including traditional uorescent in situ hybridization (FISH) [17], as well as emerging Illumina SNP genotyping arrays, nextgeneration sequencing technologies [14,16], qPCR[18], multiplex uorescent PCR [19], and the rst absolute quanti cation of LOY percentage using droplet digital PCR (ddPCR) given by Danielsson et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is a prevalent disorder that affects over 15% of couples worldwide, with various causes such as meiotic arrest due to cytogenetic shuffling, toxins, and other physical factors ( 1 4 ). Among the genetic causes of male infertility, chromosomal abnormalities have been reported in approximately 6% of cases, and microdeletions in the Y chromosome account for spermatogenic failure in 5-20% of men with azoospermia ( 3 , 5 8 ). The most common structural Y chromosome aberrations in infertile men with azoospermia have been reported to be an isodicentric or isochromosome Y, with duplications in the Yp region and deletions in the Yq region, or vice versa ( 9 12 ).…”
mentioning
confidence: 99%